Mitigating and adapting to climate change: the role of nature-based solutions in sustaining vegetation health in the Isiukhu River Basin - Tela, Samuel Abuyeka; Masayi, Nelly Nambande; Tsingalia, Mugatsia (Frontiers in Climate, 2026)
NbS are increasingly recognized for their ability to bolster ecosystem resilience and alleviate climate change impacts. This study evaluated the relationship between these solutions and vegetation health in the River Isiukhu Basin, using the NDVI to assess their effectiveness in addressing climate challenges. Focusing on the period from 1990 to 2023, the research analysed shifts in NDVI alongside temperature and precipitation patterns in the basin, while evaluating how NbS such as afforestation acted as moderating factors. Four key afforestation projects were instrumental in the region. Data on NDVI were sourced from Google Earth Engine and ArcGIS Pro 3.2, while precipitation and temperature information were obtained from the Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS) and TERRACLIMATE, respectively. The interactions among NbS, NDVI, temperature, and precipitation were analysed using Pearson correlation at a 95% confidence level. Findings revealed that afforestation NbS significantly impacted vegetation health and climate conditions. Notably, NDVI in the Isiukhu basin increased by 39.86% from 1990 to 2023, coinciding with a 22.8% rise in precipitation (an increase of 428.53 mm) and a 7.33% increase in mean annual temperature (1.48 °C). A strong positive correlation was identified between NDVI and precipitation (r = 0.6105, p = 0.000), while the relationship between NDVI and mean annual temperature was negative and non-significant (r = −0.006539, p = 0.9737). Therefore, sustaining vegetation health through NbS is not only an ecological necessity but also a strategic policy pathway for mitigating climate change impacts, enhancing sustainable landscape management, and securing long-term ecosystem services in climate-vulnerable Isiukhu River Basin.